SURVIVING TRADITIONAL VILLAGE HERITAGE IN RAPID URBANIZATION: THE CASE OF KAJANG TOWN - Hafez Zainudin; Aloysius Yapp (INTERNATIONAL JOURNAL OF HERITAGE, ART AND MULTIMEDIA (IJHAM), 2024)
The Greater Kuala Lumpur development initiative by the Malaysian government which began in 2010 has brought a tremendous economic benefits and opportunities for the people of Kuala Lumpur and its surrounding towns. However, this ambitious project has also altered the physical landscape of traditional villages in the neighbouring areas as well as the lifestyle of people affected. Kajang town is one of the smaller towns located in the outskirts of Kuala Lumpur city affected by the development. The purpose of this paper is to investigate the surviving and remaining cultural heritage among traditional village communities in Kajang and to identify the promising cultural heritage that can be preserved digitally. The study was focused on traditional cultural ceremonies which are still being practiced by communities in villages located along Jalan Cheras, which were directly affected by the Sungai Buloh-Kajang (SBK) MRT project which is apart of the Greater Kuala Lumpur development. This project has impacted the lifestyle and activities of the villagers and there are risks of cultural heritage loss among these communities. Qualitative research method was employed through discussions and interviews with the local community, village elders, local museum curator and through visits and observation of the remaining villages. The result suggests that some of the loss of natural heritage such as orchards and rivers have led to the loss of cultural heritage of villagers in ceremonial activities. However, there are also opportunities towards the preservation of the cultural heritage of Kajang villages through new media identified through this study, considering the positive support from youths towards cultural activities. The result acquired from this study will be used to further develop research work on digitization of tangible cultural heritage of this unique town.